Bone Regeneration of Maxillary Molar Proximal Class 2 Furcation Defects Treated With Microscope‐Assisted Papilla Preservation Technique and DFDBA: A Case Series. Issue 2 (23rd January 2021) - Do, Jonathan H.
Abstract : Introduction: Periodontal regeneration of maxillary molar proximal furcation defects are challenging due to limited access. While combination therapy of open flap debridement with barrier membrane, bone graft, and biologics are reported to be more successful than monotherapeutic approaches, combination therapy can be complicated and costly. Case Presentation: A total of four teeth in three patients are presented to demonstrate radiographic bone regeneration of deep Class 2 maxillary molar proximal furcation defects (MMPFD) treated with microscope‐assisted papilla preservation technique (PPT) and demineralized freeze‐dried bone allograft (DFDBA). Conclusion(s): Radiographic bone regeneration of deep Class 2 MMPFD is possible with microscope‐assisted PPT and DFDBA. Furthermore, treatment outcomes appear to be superior to those from previous clinical trials of Class 2 MMPFD treatment.